2017
DOI: 10.5964/psyct.v10i1.224
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness: Age and gender differences on a Bosnian sample

Abstract: The goal of this research was to examine age and gender differences in mindfulness on Bosnian general population. The study was conducted on a sample of 441 participants from the general population, from twelve cities in Bosnia and Herzegovina. As a measure of mindfulness we used Five Factor Mindfulness Questionnaire. Results showed that older participants' scores were higher than for younger participants for all aspects of mindfulness. There was found a statistically significant difference between the three a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 21 publications
4
21
1
4
Order By: Relevance
“…Typically, spiritual training is better received by women (Katz & Toner, 2013), well educated, upper class older adults in good health (Sperduti, Makowski, Blonde´, & Piolino, 2017), though this may also be the older adult profile that engages in volunteer work (Musick & Wilson, 2008). In the context of Bosnia and Herzegovina, Alispahic and Hasanbegovic-Anic (2017) also found that in a mindfulness training programme, older participants (60þ years) scored higher on all five factors of mindfulness (observing, describing, acting with awareness, nonjudging of inner experience and nonreactivity to inner experience) in comparison to the younger participants. Older adults have greater capacity to live in the moment and savour the present (Mogilner, Kamvar, & Aaker, 2011).…”
Section: Introductionmentioning
confidence: 67%
“…Typically, spiritual training is better received by women (Katz & Toner, 2013), well educated, upper class older adults in good health (Sperduti, Makowski, Blonde´, & Piolino, 2017), though this may also be the older adult profile that engages in volunteer work (Musick & Wilson, 2008). In the context of Bosnia and Herzegovina, Alispahic and Hasanbegovic-Anic (2017) also found that in a mindfulness training programme, older participants (60þ years) scored higher on all five factors of mindfulness (observing, describing, acting with awareness, nonjudging of inner experience and nonreactivity to inner experience) in comparison to the younger participants. Older adults have greater capacity to live in the moment and savour the present (Mogilner, Kamvar, & Aaker, 2011).…”
Section: Introductionmentioning
confidence: 67%
“…Firstly, the study aims to assess the levels of depressive symptomology and stress reactivity in a sample of TCKs. Past research, in general, has reported gender differences in depression (Nolen-Hoeksema, 1987), stress reactivity (Wang, 2007) and trait mindfulness (Alispahic & Hasanbegovic-Anica, 2017). It will be useful to examine if such patterns are observed in TCKs too.…”
Section: Current Studymentioning
confidence: 99%
“…This result is in contrast with previous findings demonstrating that higher mindfulness is influenced by the increasing age of parents. Alispahic & Hasanbegovic-Anic found that adults are more able to manage and regulate their emotions [10]. Increasing age means maturation change indicated by parents' ability to be more present because they are not interrupted by their intense emotions.…”
Section: Results Of Demographic Data Analysismentioning
confidence: 99%
“…Others findings also revealed that gender differences could be explained by cognitive functioning. Women generally are much better in observing details so it is highly likely for them to be more aware with their emotions and minds [10].…”
Section: Mindful Parentingmentioning
confidence: 99%